2015
DOI: 10.1093/database/bav023
|View full text |Cite
|
Sign up to set email alerts
|

LOTUS-DB: an integrative and interactive database for Nelumbo nucifera study

Abstract: Besides its important significance in plant taxonomy and phylogeny, sacred lotus (Nelumbo nucifera Gaertn.) might also hold the key to the secrets of aging, which attracts crescent attentions from researchers all over the world. The genetic or molecular studies on this species depend on its genome information. In 2013, two publications reported the sequencing of its full genome, based on which we constructed a database named as LOTUS-DB. It will provide comprehensive information on the annotation, gene functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Although several studies have shown that centromeric heterochromatin is incompatible with gene expression (Schmid et al ., ; Lomiento et al ., ), the existence of active genes at the CenH3 subdomain in certain plant species has been proposed (Yan et al ., ; Gong et al ., ; Li et al ., ). Based on the lotus genome annotation database from LOTUS‐DB (Wang et al ., ), 210 annotated non‐transposable element (non‐TE) genes were discovered in NnCBSs (Figure S4; Table S1) in the present study. Of these genes, 92% (194 of 210) were located in the NnH3 (Histone H3 protein in sacred lotus) subdomains, and 7% (15 of 210) of the NnCBS‐associated genes were in the NnCenH3 subdomains; gene NNU_08544 (indicated by green and red arrows in Figure a, megascaffold 47) crossed both subdomain regions in megascaffold 47.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Although several studies have shown that centromeric heterochromatin is incompatible with gene expression (Schmid et al ., ; Lomiento et al ., ), the existence of active genes at the CenH3 subdomain in certain plant species has been proposed (Yan et al ., ; Gong et al ., ; Li et al ., ). Based on the lotus genome annotation database from LOTUS‐DB (Wang et al ., ), 210 annotated non‐transposable element (non‐TE) genes were discovered in NnCBSs (Figure S4; Table S1) in the present study. Of these genes, 92% (194 of 210) were located in the NnH3 (Histone H3 protein in sacred lotus) subdomains, and 7% (15 of 210) of the NnCBS‐associated genes were in the NnCenH3 subdomains; gene NNU_08544 (indicated by green and red arrows in Figure a, megascaffold 47) crossed both subdomain regions in megascaffold 47.…”
Section: Resultsmentioning
confidence: 59%
“…The annotated gene expression (FPKM) was obtained from the transcript file of the reference sacred lotus genome, LOTUS‐DB 1.0 (http://lotus-db.wbgcas.cn; Wang et al ., ). The transcription levels of 16 NnCenH3‐associated genes were verified by RT‐PCR.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Variant calling from lotus re-sequencing data To identify variants from lotus samples, the clean resequencing reads were mapped to the lotus reference genome 'China Antique' (http://lotus-db.wbgcas.cn/) by the BWA with 'mem' method and the parameters of '-t 10 -k 32-M' (Li and Durbin 2010;Wang et al 2015). The sam files from BWA were converted to bam format by samtools (Li et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Source of datasets for the 30 species included in this study. 1KP, 1000 Green Plant Transcriptome Project [118]; AAGP, Ancestral Angiosperm Genome Project [119], Lotus-DB [120,121], Phytozome [122,123]. (5) 107 (40) 19 (4) 61 (30) 102 (55) 16 ( and paralogous gene lineages have assumed roles in floral symmetry, regulation of vegetative branching and unknown functions in flowers [131][132][133][134].…”
Section: Implications Of Gamma Palaeohexaploidymentioning
confidence: 99%